Experimental model of portal hypertension and esophagogastric varices in minipigs: pressure and endoscopic pilot study - Maluf-Filho,Fauze (2022)
ABSTRACT Introduction: Portal hypertension still represents an important health problem worldwide. In the search for knowledge regarding this syndrome, experimental studies with animal models have proven to be useful to point the direction to be taken in future randomized clinical trials. Purpose: To validate the experimental model of portal hypertension and esophagogastric varices in a medium-sized animal. Methods: This study included five minipigs br1. Midline laparotomy with dissection of the portal vein and production of a calibrated stenosis of this vein was performed. Measurement of pressure in the portal venous and digestive endoscopic were performed before and five weeks after the production of a stenosis. Results: All animals were 8 months old, average weight of 17 ± 2.5 kg. The mean pressure of the portal vein immediately before the partial ligation of the portal vein was 8.9 + 1.6 mm Hg, with 26.6 + 5.4 mm Hg in the second measurement five weeks later (p < 0.05). No gastroesophageal varices or hypertensive portal gastropathy were seen at endoscopy procedures in our sample at any time in the study. Conclusion: Portal vein ligation in minipigs has been validated in the production of portal hypertension, but not in the formation of esophageal varices.